Peran Civitas Akademika Dalam Pembangunan Hukum Nasional - Rosalina, Maria; Faisal, Muhammad; Saragih, Novi Yanti (Universitas Islam Sumatera Utara, 2024)
National law has an order of related legal systems. Law has an important role in regulating the order of society which is also interrelated with the development of the development of national law. The development of national law carried out by a country can be carried out with the existence of quality human resources which can be obtained through education. The academic community is the community within the university environment which consists of lecturers and students. The academic community has a relationship with national law because the academic community is part of the community which includes organized life, and plays a role in the formation of quality human resources. Another role of the academic community is to form programs to assist the government, such as making regional regulations in the area around the university. Then the role that can be carried out by students and lecturers is to be able to provide counseling regarding national law and open public legal awareness so that the goals of developing national law can run according to its provisions. In carrying out its role, the academic community certainly experiences obstacles or obstacles. Obstacles that may be faced are that it is difficult for the community to receive counseling regarding national law because their thinking is already bad about the development of national law or other obstacles encountered are such as making programs to help the government to make regional regulations, the government does not just glance directly at it so that the program develops it takes a short amount of time. Keyword : The Role of the Academic Community, Development, National Law, Universities